Clinicopathological and molecular features of malignant optic pathway glioma in an adult. Issue 1 (January 2015) - Nagaishi, Masaya; Sugiura, Yoshiki; Takano, Issei; Tanaka, Yoshihiro; Suzuki, Kensuke; Yokoo, Hideaki; Hyodo, Akio
Abstract Malignant gliomas of the optic pathway are rare, and their genetic alterations are poorly understood. We describe a 64-year-old woman with anaplastic astrocytoma originating from the optic pathway, together with the molecular features. She presented with progressive visual field loss, and a biopsy sample was obtained from the lesion in the optic chiasm. She underwent radiosurgery concomitant with temozolomide chemotherapy, and subsequently remained stable for 10 months after initial presentation. Molecular analysis indicated that the mass may have shared common molecular genetic features with conventional primary astrocytic gliomas but not pilocytic gliomas, which supported the morphologic diagnosis of anaplastic astrocytoma. Molecular analysis of malignant optic pathway gliomas in adults is useful for distinguishing between high-grade gliomas and anaplastic pilocytic astrocytomas, and for determining further therapy.